PROFIL SOSIAL EKONOMI DAN EKOLOGI TIGA KOMUNITAS TRANSMIGRASI DI KAWASAN TOLIWANG HALMAHERA UTARA PASCA KONFLlK - Widiono, Septri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The article describes community map by using socio-economic and ecological profile method in three communities at Toliwang, Halmahera Utara post-conflict. Based on the research, it was concluded that ecological capital have main potentially while social, money, physical and human capital need strengthening by assistance. The running of community empowerment has to be based on participatory and sustainability principal so that the conflict potential sources should be considered. They involve local power relation, ethnic and'religion different, institutional aspect, and land tenure.